A method for preparing a chromium-containing reinforced boron nitride-based thin strip continuous casting ceramic side seal plate

CN123003304APending Publication Date: 2026-10-30SINOSTEEL LUOYANG INSTITUTE OF REFRACTORIES RESEARCH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611453218.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提出一种含铬增强型氮化硼基薄带连铸陶瓷侧封板的制备方法,使其能克服传统热压BN-ZrO2-SiC侧封板高温稳定性差、抗侵蚀与抗磨损难以协同、使用寿命短等缺陷

Benefits of technology

(1) 采用CaO-B2O3新型促烧剂,耦合热压应力场协同致密化,在较低烧结温度与压力下即可实现h-BN 高致密度烧结与鳞片定向择优生长,既降低热压模具损耗与生产能耗,又避免杂质元素析出风险,适配超洁净钢、高端合金钢连铸的高要求。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application belongs to the technical field of double-roller thin strip continuous casting functional refractory ceramic materials, and relates to a preparation method of a chromium-containing reinforced boron nitride-based thin strip continuous casting ceramic side sealing plate. The preparation method comprises the steps of raw material pretreatment, accurate batching, wet mixing, drying and powdering, hot pressing and sintering, finishing and finished product detection. 6 The chromium-containing reinforced boron nitride-based thin strip continuous casting ceramic side sealing plate raw material comprises, by mass percentage, hexagonal boron nitride powder 45-52wt%, alpha-alumina powder 36-45wt%, chromium sesquioxide powder 4-8wt%, B4C 2-4wt%, CaB h 6wt%, CaO-B2O3 binary system 1-2wt%, and the total mass is 100%. h The present application uses hexagonal boron nitride (-BN) as a matrix phase, combines Al2O3, Cr2O3 and B4C / CaB6 wear-resistant and corrosion-resistant phases, introduces CaO-B2O3 type composite sintering agent, realizes -BN densification sintering through a hot pressing and sintering process, and has the characteristics of excellent resistance to molten steel corrosion, resistance to casting roll / strip wear, high-temperature oxidation resistance and thermal shock resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of functional refractory ceramic materials for twin-roll thin strip continuous casting, specifically relating to a method for preparing a chromium-reinforced boron nitride-based thin strip continuous casting ceramic side sealing plate. Background Technology

[0002] Twin-roll thin strip continuous casting technology, with its outstanding advantages of short process, low energy consumption, and near-net-shape forming, has become the core development direction of high-end thin strip steel manufacturing. As the core sealing component of the thin strip continuous casting unit, the side sealing plate directly determines the stability of the molten pool, the quality of the thin strip edge, and the continuous casting operation rate. During its service, it faces multiple coupled extreme working conditions: the working surface is in long-term contact with molten steel at temperatures above 1500°C, and is subjected to chemical corrosion and penetration by molten steel and alloying elements; at the same time, it is subject to continuous dynamic friction with the end face of the high-speed rotating casting roll and the edge of the solidified thin strip, accompanied by severe alternating thermal shock and high-temperature oxidation during the casting start-up and shutdown process; as thin strip continuous casting upgrades towards high casting speed, ultra-clean steel, and special alloy steel, higher requirements are placed on the density, high-temperature strength, and multi-performance synergy of the side sealing plate.

[0003] Currently, most mainstream industrial BN-ZrO2-SiC multiphase side sealing plates are prepared by hot pressing sintering. Although this can achieve a certain density, it still has many shortcomings that make it difficult to adapt to high-end working conditions: First, the system composition and high-temperature stability are insufficient. At high temperatures, the SiC phase is prone to interfacial reactions with active alloying elements in steel, generating low-melting-point phases and promoting the sintering and growth of ZrO2 to form nodules; the ZrO2 phase has a crystal transformation volume effect, and is prone to microcracks under repeated thermal shocks, and is easily reduced by active elements in molten steel, resulting in a rapid decline in structural stability and anti-permeability as service time increases. Second, the hot pressing sintering aid system has inherent defects. Existing hot-pressed BN ceramics mostly use rare earth oxide-based sintering accelerators, which have high raw material costs, and the resulting grain boundary glass phase is prone to softening and creep at high temperatures, leading to a sharp drop in the high-temperature load-bearing capacity and wear resistance of the side sealing plate; ordinary sintering systems cannot fully utilize the stress field induced by hot pressing. h - The directional development of BN flakes prevents the full realization of the matrix's anisotropic advantages, resulting in significant bottlenecks in improving its resistance to permeation and thermal shock. Thirdly, the synergy of multiple properties is poor. Existing systems struggle to simultaneously achieve a balance between high density, high erosion resistance, and high wear resistance: increasing the proportion of hard phases disrupts the non-metallic wettability of BN, exacerbating the risk of steel adhesion; optimizing wettability and erosion resistance leads to insufficient matrix strength and increased wear rate; frequent cleaning of deposits on the working surface severely restricts the production continuity and service life of high-speed continuous casting.

[0004] To address the aforementioned industry pain points, this invention develops a chromium-reinforced boron nitride-based ceramic side sealing plate prepared by hot pressing sintering. It employs a CaO-B₂O₃ sintering system, combined with hot pressing stress field induction. h-BN flakes are directionally grown and combined with Cr2O3 to form a highly stable chromium-aluminum solid solution reinforcing phase in situ. While achieving high-density sintering, it simultaneously improves the resistance to erosion, wear, oxidation and thermal shock. The working surface is clean and free of adhering substances for a long time, which is suitable for the production needs of high-speed thin strip continuous casting of high-end steel grades. Summary of the Invention

[0005] The purpose of this invention is to propose a method for preparing a chromium-enhanced boron nitride-based thin strip continuous casting ceramic side sealing plate, which can overcome the defects of traditional hot-pressed BN-ZrO2-SiC side sealing plates, such as poor high-temperature stability, difficulty in coordinating corrosion resistance and wear resistance, and short service life.

[0006] This method employs a vacuum-nitrogen protected hot-pressing sintering process. Through the synergistic effect of CaO-B2O3 binary sintering accelerator and axial pressure, high-density sintering of h-BN and preferential development of scale are achieved. Cr2O3 is introduced in situ to generate a highly stable chromium-aluminum solid solution reinforcing phase, constructing a multi-scale synergistic reinforcement system. This simultaneously improves resistance to molten steel erosion, friction and wear, high-temperature oxidation, and thermal shock, while maintaining a clean working surface and significantly extending the overall service life.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a chromium-reinforced boron nitride-based thin strip continuously cast ceramic side sealing plate includes the following steps: raw material pretreatment, precise batching, wet mixing, drying and powdering, hot pressing and sintering, finishing and finished product testing, as detailed below: 1) Raw material pretreatment: Hexagonal boron nitride powder, α-alumina powder, chromium trioxide powder, and boride powder (CaB6) were selected and pretreated respectively: hexagonal boron nitride powder was vacuum dried at 120℃ for 2 hours to remove adsorbed moisture and gas; α-alumina powder and chromium trioxide powder were calcined at 1000℃ for 2 hours to remove crystal water and impurities and improve crystallinity; boride powder and composite sintering accelerator were dispersed and deagglomerated by air jet milling to control uniform particle size distribution; all raw materials were screened under negative pressure to remove large particles and foreign impurities. 2) Ingredients: The raw material for chromium-reinforced boron nitride-based thin strip continuous casting ceramic side sealing plates is composed of the following mass percentages, with a total mass of 100%; Hexagonal boron nitride powder ( h -BN) 45~52wt%, α-alumina powder 36~45wt%; chromium trioxide powder 4~8wt%; B4C 2-4wt%, CaB6 3~6wt%; sintering accelerator CaO-B2O3 binary system 1-2wt%; 3) Preparation process: Follow these steps: (1) Dry mixing stage: The pretreated material is mixed with the dry material.h - Add BN powder, alumina powder, chromium trioxide powder, boride reinforcing phase, and composite sintering accelerator to a high-speed high-power mixer according to the specified ratio, and dry mix at 550~750 r / min for 18~28 min to ensure that each solid phase component is uniformly dispersed and free from agglomeration and segregation; (2) Wet mixing: The dry mixture is transferred to a planetary ball mill, anhydrous ethanol is added, and silicon nitride balls are used as the grinding medium. The ball-to-material mass ratio is 2.5:1. Wet ball milling is carried out at a speed of 350~550r / min for 5~9h to obtain a uniformly dispersed mixed slurry. (3) Drying and powdering: The slurry after ball milling is placed in a vacuum drying oven and dried at 60~80℃ to remove anhydrous ethanol. After crushing, it is passed through a 100-mesh sieve to obtain a uniformly mixed sintered powder. (4) Hot pressing sintering: The sintering powder is loaded into a graphite mold with graphite paper attached to the inner wall and placed in a vacuum hot pressing sintering furnace. First, the vacuum is evacuated to below 10 Pa, and the temperature is raised to 1000°C at 5~10°C / min. Then, high-purity nitrogen is introduced to maintain a slight positive pressure protection. The temperature is further raised to 1700~1800°C at 4~7°C / min, and axial pressure of 20~30MPa is applied simultaneously. The temperature and pressure are maintained for 1~3 hours. After the heat preservation is completed, the pressure is first removed, and then the furnace is cooled to room temperature before the sintered blank of the side sealing plate is taken out. During hot pressing sintering, the axial mechanical pressure and the low-melting-point calcium-boron liquid phase formed by CaO-B2O3 work synergistically to significantly accelerate the densification process through multiple mass transfer mechanisms including particle rearrangement, plastic deformation, and dissolution-precipitation; simultaneously, the axial stress field induces… h -BN crystals grow with a preferred orientation along the basal plane perpendicular to the pressure direction, forming a highly ordered, oriented, stacked lamellar structure: oriented... h The BN layered stacked structure efficiently dissipates heat stress through inter-laminar slip and crack deflection, and also acts as a lubricant, reducing wear on the sides of the casting roll. The micron-sized B4C / CaB6 non-oxide hard phase improves the material's wear resistance and also acts as an antioxidant, protecting it. h -BN, thereby improving corrosion resistance; during high-temperature sintering, Cr2O3 and Al2O3 react in situ to generate a continuous solid solution of chromium aluminum solid solution (Cr,Al)2O3 phase, which is uniformly dispersed in the BN matrix, enhancing the resistance to strip corrosion and wear. (5) Finished product: The hot-pressed sintered blank is precision ground by CNC according to the side sealing plate size drawing. The allowable deviation of the dimensions conforms to the standard of boron nitride-based side sealing plate for twin-roll thin strip continuous casting (T / CISA491-2024). After cleaning, appearance inspection, dimensional inspection and non-destructive testing, the finished side sealing plate is obtained.

[0008] The purity of the hexagonal boron nitride powder is ≥99wt%, and the particle size is 5~15μm.

[0009] The α-alumina powder contains Al2O3 ≥ 99.5 wt% and has a particle size of 1~3 μm.

[0010] The chromium trioxide powder contains Cr2O3 ≥ 99wt% and has a particle size of 2~5μm.

[0011] The purity of the B4C is ≥98wt%, and the particle size is 2~5μm.

[0012] The purity of the CaB6 is ≥98wt%, and the particle size is 2~5μm; The particle size of the CaO-B2O3 binary system of the sintering accelerator is <10μm; the sintering accelerator is one of CaO-B2O3, 2CaO-B2O3, and 3CaO-B2O3.

[0013] This invention employs a CaO-B2O3 accelerated sintering system coupled with a hot-compression stress field to synergistically achieve... h -BN high-density sintering and directional flake growth, combined with Cr2O3 in-situ reinforcing phase design, achieve synergistic performance upgrades of the side sealing plate from five dimensions: sintering densification, erosion resistance, wear resistance, oxidation resistance, and thermal shock resistance. (1) Mechanism of thermal stress-liquid phase mass transfer synergistic densification and scale directional control: During hot pressing sintering, the axial mechanical pressure and the low-melting-point calcium-boron liquid phase formed by CaO-B2O3 work synergistically to significantly accelerate the sintering densification process through multiple mass transfer mechanisms such as particle rearrangement, plastic deformation, and dissolution-precipitation. The apparent porosity of the finished product is reduced to below 3%, and the matrix density and structural uniformity are significantly better than those of the atmospheric pressure sintering system. At the same time, the axial stress field induces… h -BN crystals are preferentially oriented along the basal plane perpendicular to the pressure direction, increasing the average lamellar diameter by more than 60% and forming a highly ordered lamellar stacking structure. On the one hand, this significantly extends the penetration path of molten steel, greatly improving the resistance to molten steel penetration and erosion; on the other hand, it strengthens the matrix by directional lamellar slip, simultaneously improving the fracture toughness and thermal shock resistance; in addition, the ordered lamellars impart anisotropic solid lubrication properties to the working surface, effectively reducing the friction and wear rate.

[0014] (2) In-situ strengthening and anti-erosion mechanism of chromium-aluminum solid solution:

[0015] During high-temperature sintering, Cr2O3 reacts in situ with Al2O3 to form a continuous solid solution of chromium-aluminum (Cr,Al)2O3 phase, which is uniformly dispersed in the BN matrix. This solid solution phase has high hardness and extremely strong chemical inertness, and hardly undergoes dissolution or interfacial reaction in alloy steel containing Cr, Ni, and Mn, as well as in ultra-low carbon clean steel, which can significantly resist the penetration and erosion of steel and alloying elements. At the same time, the solid solution phase fills the grain boundary pores, and combined with the high density brought about by hot pressing, it double-blocks the penetration channels of steel, reducing the erosion depth of steel by more than 45%. In addition, Cr2O3 can moderately adjust the slag-steel interfacial tension, further reducing the adhesion tendency of steel and inclusions on the working surface, ensuring that the working surface is clean and free of nodules for a long time.

[0016] (3) Dual-scale synergistic anti-wear mechanism:

[0017] A three-tiered wear-resistant system is constructed, consisting of "grain boundary ceramic phase reinforcement + micron-sized hard phase support + directional lamellar lubrication": the micron-sized B4C / CaB6 hard phase acts as the main support phase, resisting macroscopic cutting wear on the casting roll end face and the thin strip edge; the aluminum-chromium solid solution further inhibits microscopic ploughing and spalling wear; and the directionally arranged... h -BN layers provide anisotropic solid lubrication, stabilizing the coefficient of friction and reducing adhesive wear; the combined effect of these three factors achieves synergistic optimization of resistance to molten steel erosion and frictional wear, making it suitable for the high-wear conditions of high-speed continuous casting.

[0018] (4) Multi-level high-temperature antioxidant protection mechanism:

[0019] A multi-layered anti-oxidation structure is formed, consisting of "surface boride passivation + subsurface chromium oxide densification + matrix BN stabilization": Under high-temperature and aerobic conditions, the surface B4C / CaB6 preferentially oxidizes to form B2O3. In the traditional side sealing plate molten pool area, BN oxidized to B2O3 is easily volatilized directly, but Cr2O3 can inhibit the high-temperature volatilization of B2O3; in the strip area, because the temperature is low, B2O3 is not easily volatilized and can play a lubricating role; the internal high-density BN matrix has a significantly reduced oxidation rate due to the effective blockage of oxygen; after static oxidation at 1000℃ for 10 hours, the oxidation weight gain is less than 0.6 mg / cm², and the anti-oxidation performance is significantly better than that of the traditional SiC-containing system.

[0020] (5) Multi-mechanism coupling thermal shock resistance mechanism:

[0021] Oriented arrangement h- The layered structure of BN efficiently dissipates heat stress through interlaminar slip and crack deflection; the thermal expansion coefficient of the in-situ generated chromium-aluminum solid solution is well matched with that of the BN matrix, avoiding interfacial cracking during thermal cycling; the system does not contain ZrO2 phase transformation components, eliminating the thermal shock damage source caused by the volume effect of crystal transformation; at the same time, the high density brought by hot pressing and the strengthening of the grain boundary ceramic phase further suppress the propagation of thermal shock cracks; it can withstand more than 35 water-cooled thermal shock cycles at 1000℃, and the strength retention rate after thermal shock is greater than 90%, demonstrating excellent thermal shock resistance.

[0022] The present invention proposes a method for preparing a chromium-reinforced boron nitride-based thin strip continuously cast ceramic side sealing plate. Using the above-mentioned technical solution, it has the following beneficial effects: (1) A novel sintering accelerator, CaO-B2O3, is used to achieve densification through coupled hot-compression stress field, which can be achieved at relatively low sintering temperature and pressure. h -BN's high-density sintering and preferential growth of scales reduce hot pressing mold wear and production energy consumption, while avoiding the risk of impurity element precipitation, making it suitable for the high requirements of continuous casting of ultra-clean steel and high-end alloy steel.

[0023] (2) Introducing Cr2O3 to generate chromium-aluminum solid solution reinforcement phase in situ, combined with the high density advantage of hot pressing, greatly improves the chemical stability of the matrix and its resistance to molten steel corrosion. There are no obvious steel adhering substances on the working surface, and the defect rate of the thin strip edge is significantly reduced.

[0024] (3) Construct a three-level synergistic wear-resistant system, combined with h The lubricating effect of the oriented BN layers simultaneously improves the resistance to frictional wear of casting rolls and the resistance to cutting wear of thin strips. The high hardness of the chromium-aluminum solid solution significantly reduces the wear rate compared to the traditional hot-pressed BN-ZrO2-SiC system, achieving a synergistic effect of corrosion resistance and wear resistance.

[0025] (4) The multi-level anti-oxidation structure and multi-mechanism thermal shock stability design optimize the high-temperature anti-oxidation and thermal shock resistance of the side sealing plate, and improve the overall service life by more than 30% compared with the traditional system, thus greatly improving the production efficiency of thin strip continuous casting.

[0026] (5) The hot-pressed sintered billet has a uniform microstructure and excellent mechanical properties, with small allowance for subsequent finishing and high yield; the system is free of fluorine and toxic and harmful components, and the service process is clean and environmentally friendly, meeting the requirements of green and low-carbon production of high-end steel grades.

[0027] In summary, this invention uses hexagonal boron nitride ( h Using BN as the matrix phase, a composite of Al2O3, Cr2O3, and B4C / CaB6 wear-resistant and corrosion-resistant phases is formulated, and a CaO-B2O3 type composite sintering accelerator is introduced. The process is achieved through hot pressing sintering. h-BN densification sintering has the characteristics of excellent resistance to molten steel corrosion, resistance to casting roll / strip wear, high temperature oxidation resistance and thermal shock resistance. Detailed Implementation

[0028] The invention will be described in detail with reference to specific embodiments: Example 1: Ingredient ratio (mass fraction): h -BN powder 52%, α-alumina powder 36%, chromium trioxide powder 4%, B4C powder 3%, CaB6 powder 4%, sintering accelerator CaO·B2O3 1%.

[0029] Process parameters: dry mixing for 20 min, wet ball milling for 6 h, vacuum drying at 80℃ and passing through a 100-mesh sieve; hot pressing sintering vacuum degree of 8 Pa, nitrogen protection at 1000℃, sintering temperature of 1750℃, axial pressure of 25 MPa, heat and pressure holding for 2 h, and furnace cooling.

[0030] Performance testing: Bulk density 2.71 g / cm³ 3 It has an apparent porosity of 0.2%, a compressive strength of 168 MPa at room temperature, and a flexural strength of 13 MPa at 1400℃; the static oxidation weight gain after 1000℃×10h is 0.59 mg / cm³. 2 No cracking occurred after 36 cycles of water-cooled thermal shock at 1000℃; the corrosion rate was 1.3mm after 1 hour of immersion in molten steel in a medium-frequency furnace using a rotating method, and there were no obvious steel-adhering substances on the working surface.

[0031] Example 2: Ingredient ratio (mass fraction): h -BN powder 45%, α-alumina powder 38%, chromium trioxide powder 5%, B4C powder 4%, CaB 66%, 3CaO·B2O3 composite sintering accelerator 2%.

[0032] Process parameters: dry mixing for 20 min, wet ball milling for 6 h, vacuum drying at 80℃ and passing through a 100-mesh sieve; hot pressing sintering vacuum degree 2 Pa, nitrogen protection at 1000℃, sintering temperature 1760℃, axial pressure 20 MPa, heat and pressure holding for 3 h, and furnace cooling.

[0033] Performance testing: Bulk density 2.75 g / cm³ 3 It has an apparent porosity of 0.1%, a compressive strength of 135 MPa at room temperature, and a flexural strength of 14.3 MPa at 1400℃; the static oxidation weight gain after 1000℃ for 10 hours is 0.42 mg / cm³. 2 No cracking occurred after 33 cycles of water cooling and thermal shock at 1000℃; the corrosion rate was 0.8mm after 1 hour of immersion in molten steel in a medium-frequency furnace using a rotating method, and there were no obvious steel-adhering substances on the working surface.

[0034] Example 3: Ingredient ratio (mass fraction): h -BN powder 46%, α-alumina powder 36%, chromium trioxide powder 8%, B4C powder 4%, CaB6 4.5%, CaO·B2O3 composite sintering accelerator 1.5%.

[0035] Process parameters: dry mixing for 20 min, wet ball milling for 6 h, vacuum drying at 80℃ and passing through a 100-mesh sieve; hot pressing sintering vacuum degree 2 Pa, nitrogen protection at 1000℃, sintering temperature 1800℃, axial pressure 30 MPa, heat and pressure holding for 1 h, and furnace cooling.

[0036] Performance testing: Bulk density 2.76 g / cm³ 3 It has an apparent porosity of 0.2%, a compressive strength of 168 MPa at room temperature, and a flexural strength of 13 MPa at 1400℃; the static oxidation weight gain after 1000℃×10h is 0.48 mg / cm³. 2 No cracking occurred after 36 cycles of water-cooled thermal shock at 1000℃; the corrosion rate was 1.2mm after 1 hour of immersion in molten steel in a medium-frequency furnace using a rotating method, and there were no obvious steel-adhering substances on the working surface.

[0037] Example 4:

[0038] Ingredient ratio (mass fraction): h -BN powder 45%, α-alumina powder 45%, chromium trioxide powder 4%, B4C powder 2%, CaB6 powder 3%, 2CaO·B2O3 composite sintering accelerator 1%.

[0039] Process parameters: dry mixing for 20 min, wet ball milling for 6 h, vacuum drying at 80℃ and passing through a 100-mesh sieve; hot pressing sintering vacuum degree of 5 Pa, nitrogen protection at 1000℃, sintering temperature of 1700℃, axial pressure of 25 MPa, heat and pressure holding for 2 h, and furnace cooling.

[0040] Performance testing: Bulk density 2.79 g / cm³ 3 It has an apparent porosity of 0.3%, a compressive strength of 136 MPa at room temperature, and a flexural strength of 12.2 MPa at 1400℃; the static oxidation weight gain after 1000℃ for 10 hours is 0.51 mg / cm³. 2 No cracking occurred after 30 cycles of water cooling and thermal shock at 1000℃; the corrosion rate was 1.1mm after 1 hour of immersion in molten steel in a medium-frequency furnace using a rotating method, and there were no obvious steel-adhering substances on the working surface.

Claims

1. A method for preparing a chromium-reinforced boron nitride-based thin strip continuously cast ceramic side sealing plate, characterized in that: The process includes raw material pretreatment, precise batching, wet mixing, drying and pulverizing, hot pressing and sintering, finishing, and finished product testing, as detailed below: 1) Raw material pretreatment: Hexagonal boron nitride powder, α-alumina powder, chromium trioxide powder, and boride powder (CaB6 reinforcing phase powder) were selected and pretreated respectively: hexagonal boron nitride powder was vacuum dried at 120℃ for 2 hours to remove adsorbed moisture and gas; α-alumina powder and chromium trioxide powder were calcined at 1000℃ for 2 hours to remove crystal water and impurities and improve crystallinity; boride powder and composite sintering accelerator were dispersed and deagglomerated by air jet milling to control uniform particle size distribution; all raw materials were screened under negative pressure to remove large particles and foreign impurities. 2) Ingredients: The raw material for chromium-reinforced boron nitride-based thin strip continuous casting ceramic side sealing plates is composed of the following mass percentages, with a total mass of 100%; Hexagonal boron nitride powder h -BN 45~52wt%, α-alumina powder 36~45wt%; chromium trioxide powder 4~8wt%; B4C 2-4wt%, CaB 63~6wt%; sintering accelerator CaO-B2O3 binary system 1-2wt%; 3) Preparation process: Follow these steps: (1) Dry mixing stage: The pretreated material is mixed with the dry material. h - Add BN powder, alumina powder, chromium trioxide powder, boride reinforcing phase, and composite sintering accelerator to a high-speed high-power mixer according to the formula, and dry mix at 550~750 r / min for 18~28 min to ensure that each solid phase component is uniformly dispersed and free from agglomeration and segregation; (2) Wet mixing: The dry mixture is transferred to a planetary ball mill, anhydrous ethanol is added, and silicon nitride balls are used as the grinding medium. The ball-to-material mass ratio is 2.5:

1. Wet ball milling is carried out at a speed of 350~550r / min for 5~9h to obtain a uniformly dispersed mixed slurry. (3) Drying and powdering: The slurry after ball milling is placed in a vacuum drying oven and dried at 60~80℃ to remove anhydrous ethanol. After crushing, it is passed through a 100-mesh sieve to obtain a uniformly mixed sintered powder. (4) Hot pressing sintering: The sintering powder is loaded into a graphite mold with graphite paper attached to the inner wall and placed in a vacuum hot pressing sintering furnace. First, the vacuum is evacuated to below 10 Pa, and the temperature is raised to 1000°C at 5~10°C / min. Then, high-purity nitrogen is introduced to maintain a slight positive pressure protection. The temperature is further raised to 1700~1800°C at 4~7°C / min, and axial pressure of 20~30MPa is applied simultaneously. The temperature and pressure are maintained for 1~3 hours. After the heat preservation is completed, the pressure is first removed, and then the furnace is cooled to room temperature before the sintered blank of the side sealing plate is taken out. (5) Finished product: The hot-pressed sintered blank is precision ground by CNC according to the side sealing plate size drawing. The allowable dimensional deviation meets the standard of boron nitride-based side sealing plate for double-roll thin strip continuous casting. After cleaning, appearance inspection, dimensional inspection and non-destructive testing, the finished side sealing plate is obtained.

2. The method for preparing a chromium-reinforced boron nitride-based thin strip continuously cast ceramic side sealing plate as described in claim 1, characterized in that: The purity of the hexagonal boron nitride powder is ≥99wt%, and the particle size is 5~15μm.

3. The method for preparing a chromium-reinforced boron nitride-based thin strip continuous casting ceramic side sealing plate as described in claim 1, characterized in that: The α-alumina powder contains Al2O3 ≥ 99.5 wt% and has a particle size of 1~3 μm.

4. The method for preparing a chromium-reinforced boron nitride-based thin strip continuously cast ceramic side sealing plate as described in claim 1, characterized in that: The chromium trioxide powder contains Cr2O3 ≥ 99wt% and has a particle size of 2~5μm.

5. The method for preparing a chromium-reinforced boron nitride-based thin strip continuous casting ceramic side sealing plate as described in claim 1, characterized in that: The purity of the B4C is ≥98wt%, and the particle size is 2~5μm.

6. The method for preparing a chromium-reinforced boron nitride-based thin strip continuously cast ceramic side sealing plate as described in claim 1, characterized in that: The CaB6 has a purity of ≥98wt% and a particle size of 2~5μm.

7. The method for preparing a chromium-reinforced boron nitride-based thin strip continuous casting ceramic side sealing plate as described in claim 1, characterized in that: The particle size of the CaO-B2O3 binary system of the sintering accelerator is <10μm; the sintering accelerator is one of CaO-B2O3, 2CaO-B2O3, and 3CaO-B2O3.